A communication guide for investor relations in an age of activism - DiStaso, Marcia W. 1970-; Michaelson, David; Gilfeather, John (Public relations collection, 2018)
1. Investor relations background and history -- 2. Audiences for investor relations -- 3. Investor relations and corporate reputation -- 4. Investor relations ethics -- 5. Emerging issues in investor relations -- 6. Writing for investor relations -- 7. Corporate governance and investor relations -- 8. Proxy voting and the investor relations officer -- 9. Investor relations events -- 10. Global investor relations -- 11. Risks, corporate crises, and investor relations -- 12. Measuring investor relations -- About the authors -- Bibliography -- Index